Organizational culture dimensions in Romanian finance industry - Gheorghe-Alexandru Catanæa; Doina Catanéa (Journal for East European Management Studies, 2010)
As part of the GLOBE project, this paper explores the societal and the organizational culture of the Romanian finance industry as reflected by middle managers' opinion. The two culture levels are compared across nine cultural dimensions. The differences between the cultural manifestations (practices and values) are analyzed through comparing the middle managers' answers to 'what is' and 'what should be' type questions at organizational and societal levels. The findings show some significant differences for the majority of the cultural dimensions examined both between culture levels (organizational versus societal) and culture manifestations (practices versus values). – – Als Teil des GLOBE - Projekts erforscht dieser Artikel die soziale und organisatorische Kultur der rumänischen Finanzwirtschaft im Hinblick auf die Sichtweise des mittleren Managements. Diese zwei Kulturniveaus werden anhand von neun kulturellen Dimensionen verglichen. Die Unterschiede zwischen den kulturellen Manifestationen (Praktiken und Werte) werden durch den Vergleich der Antworten zu den Fragen auf den organisatorischen und sozialen Ebenen sowie 'Was ist' und 'Was sollte sein' analysiert, die vom mittelständischen Management erhoben ermittelt wurden. Die Ergebnisse zeigen einige signifikante Unterschiede für die Mehrheit der kulturellen Dimensionen, sowohl zwischen den kulturellen Ebenen (organisatorische vs. gesellschaftliche) als auch zwischen den kulturellen Manifestationen (Praktiken und Werte).
Keywords: 650; cultural dimensions; cultural values; cultural practices